PENGEMBANGAN GAME EDUKASI INTERAKTIF BERBASIS ANDROID MELALUI SMART APPS CREATOR (SAC) TERHADAP MISKONSEPSI IPA PESERTA DIDIK SMP - Jumanah, Jumanah; Nulhakim, Lukman; Kurniasih, Septi (PendIPA Journal of Science Education, 2026)
Misconceptions are one of the main obstacles in the junior high school science learning process, especially in the subject of the digestive system, because students often maintain incorrect understandings that impact their mastery of advanced concepts. To address this issue, this study designed an interactive Android-based educational game using Smart Apps Creator (SAC) as an alternative solution to minimize misconceptions. The main objectives of this study include testing the validity of the media produced and assessing student responses to the application of these educational games in science learning. This study applied the Research and Development (R&D) method using the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. The validation process was carried out by subject matter experts, media experts, and practitioners (junior high school science teachers) using a questionnaire instrument, while limited testing involved students through a response questionnaire. The validation results show that subject matter experts gave a score of 87.75%, media experts 94.39%, and practitioner experts 85.50%, with an average validity level of 89.21%, which falls into the “highly valid” category. Meanwhile, student responses obtained a percentage of 88.67% and were in the “very good” category, confirming that the learning media developed was not only appropriate in terms of content and appearance, but also well received by direct users, and it is recommended to be further developed with broader coverage and tested on a larger scale to obtain more comprehensive findings.